Exercise Science - Lee, B.
Lecture Notes: Anatomy & Physiology Biomechanics Exercise Physiology Exercise Physiology II Exercise Physiology III First Aid Fitness Measurement & Evaluation Scientific Foundations Testing & Prescriiptions Weight Control Weight Training